2023
DOI: 10.3390/molecules28145426
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Dietary Polyphenols through Inhibitory Activity against Metalloproteinases

Abstract: Matrix metalloproteinases (MMPs) are zinc-dependent metalloproteinases that play important roles in a variety of diseases, including cancer, cardiovascular disease, diabetes, obesity, and brain diseases. Dietary polyphenols are thought to have a variety of beneficial effects on these diseases characterized by inflammation. Clinical studies have demonstrated that MMPs are in most cases upregulated in various inflammatory diseases, including osteoarthritis, rheumatoid arthritis, inflammatory bowel disease, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 151 publications
1
4
0
Order By: Relevance
“…As a result of our experiments, RSV inhibited MMP-9 in THP-1 supernatants but not in "in-gel" zymography, suggesting that this antioxidant only exerted its inhibitory action on the expression of the enzyme. This result is consistent with previous studies showing the ability of RSV to downregulate MMP-9 expression by inhibiting the activation of the transcription factors NF-kB and AP-1 [30,40]. Differently, we found that GTE was able to inhibit, in a dose-dependent manner, both the activity and expression of MMP-2 and MMP-9 as assessed by the "in-gel" zymography and by the analysis of the THP-1 supernatants, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As a result of our experiments, RSV inhibited MMP-9 in THP-1 supernatants but not in "in-gel" zymography, suggesting that this antioxidant only exerted its inhibitory action on the expression of the enzyme. This result is consistent with previous studies showing the ability of RSV to downregulate MMP-9 expression by inhibiting the activation of the transcription factors NF-kB and AP-1 [30,40]. Differently, we found that GTE was able to inhibit, in a dose-dependent manner, both the activity and expression of MMP-2 and MMP-9 as assessed by the "in-gel" zymography and by the analysis of the THP-1 supernatants, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…At the molecular level, polyphenols may downregulate the ROS-induced activation of ERK 1/2, p38 and JNK, as well as PI3K/AKT, preventing the nuclear translocation of NF-kB and the downstream activation of the transcription factor AP-1. The consequent downregulation of MMP gene transcription results in the inhibition of tumor cell growth, metastasis, angiogenesis and inflammation [22,40,41]. As a result of our experiments, RSV inhibited MMP-9 in THP-1 supernatants but not in "in-gel" zymography, suggesting that this antioxidant only exerted its inhibitory action on the expression of the enzyme.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, studies in the literature have already suggested that the daily optimal consumption of fruits and vegetables high in polyphenol compounds decreases the risk of developing specific chronic and degenerative diseases with an inflammatory component, via MMPs regulation [ 62 , 63 , 64 ]. Accordingly, multiple studies have examined the chemical composition of the raspberry leaf extract, uncovering a wide range of bioactive compounds that have prompted research into its potential uses in several diseases, especially those related to inflammation and metabolic disorders [ 22 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This potency may be attributable to the presence of polyphenols. These components exert considerable anti-inflammatory properties, and can be regarded as contributing to their prevention [21][22][23].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%